A clinical study on the effect of programmed labor on feto-maternal outcome - CM, Veerendrakumar; Chikkagowdra, Shaila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Stress of labor pain disturbs the maternal autonomic functions and liberates catecholamines which predisposes to dysfunctional labor and compromise fetal oxygenation. Freedom from pain improves the environment for both mother and fetus and therapy improves obstetric outcome. The objective of the study was to evaluate the efficacy of programmed labor protocol in providing shorter, safer and relatively pain free deliveries. Methods: 100 primigravidae with term pregnancy (37-41 wks) meeting inclusion criteria were enrolled in the study. Alternate women were allocated to two groups-study group (50) and control group (50). Programmed labor protocol was initiated in study group and control group were managed expectantly as per hospital protocol. Feto maternal outcome variables were noted. Results: In study group there was a marked reduction of the active phase of labor. The mean duration of cervical dilatation was nearly double (2.3+/-0.3 cm/hr) than the control group (1.2+/-0.4cm/hr) resulting in shortening of the duration of both first as well as second stage in the study group. In the study there was 66% of women has good pain relief 20% of women has moderate pain relief. No neonatal mortality or life threatening complications were seen in both the groups. Conclusions: Programmed labor protocol can be used by all clinicians with high benefit and safety margin.